Analisis Pengaruh Brand Image dan Kesesuaian Harga Terhadap Minat Beli Paket Tur di Dwidaya Tour Supermal Karawaci Kabupaten Tangerang - Jessica Aprillia Chandra; Rendy Sarudin (LPPM Institut Pendidikan Nusantara Global, 2025)
This thesis analyzes the influence of brand image and price conformity on purchase intention of tour packages at Dwidaya Tour Supermal Karawaci. The background of the study lies in the intense competition within the tourism industry, which requires travel agencies to understand the key factors influencing consumer decisions. Purchase intention is considered a key indicator of marketing success, with brand image and price conformity being crucial variables shaping consumer perceptions. Using a descriptive quantitative method, the study collected data through a questionnaire survey of 80 respondents who had used the services of Dwidaya Tour Supermal Karawaci, selected via purposive sampling. Data analysis was conducted using multiple linear regression via SPSS. The results show that brand image has a positive and significant effect on purchase intention, indicating that brand trust and reputation drive purchasing behavior. Likewise, price conformity also has a positive and significant effect, suggesting that fair and competitive pricing strongly influences buying decisions. Together, these variables significantly affect purchase intention. The implication is that Dwidaya Tour should continue to strengthen its brand image through service quality and innovation, while also evaluating its pricing strategies to align with consumer value perceptions. The goal is to attract and retain customer purchase interest in a dynamic tourism market.